(untitled) (Ustozlar uchun, 2026)
Periodontal diseases are a widespread problem affecting individuals of all ages. Statistics indicate that they are diagnosed in 64% to 98% of adults and 30% to 80% of children. If left untreated, progressive periodontitis leads to tooth loss, negatively impacts systemic health, and ultimately diminishes the patient’s quality of life. The high prevalence of periodontal infections, their systemic influence, and significant tooth loss emphasize the clinical and socio-economic importance of this issue. Developing effective methods for treating inflammatory and destructive periodontal diseases remains a priority in modern dentistry. This necessity is driven by the persistence of these conditions and the complexities involved in treating chronic lesions, which require a comprehensive and highly effective therapeutic strategy.